Judicial Committee of the Privy Council – Judicial Relic of the British Empire? - Korporowicz, Łukasz Jan (The British Empire: Interdisciplinary Deliberations, 2019)
This work attempts to find an answer to a question regarding the anachronistic character of the Judicial Committee of the Privy Council. It consists of three separate parts: historical, structural and procedural. An analysis of these three aspects allows to reject the opinion that the Committee was of an anachronistic character. In other words, its structure and procedure are entrenched in the historical experience which, at first glance, may give a false impression of anachronism. Yet in fact, its present shape and form do not differ from other similar judicial bodies. The data collected over a period of the last few years show that the Committee passes around 40 decisions per year. By no means a small number for such a unique court.